Comparative Analysis of Telecommunications Infrastructure Resilience in BRICS Nations: An Integrated MCDM Approach - Chia-Nan Wang; Shao-Dong Syu; Nhat-Luong Nhieu (IEEE Access, 2024)
This study conducts a detailed evaluation of telecommunications infrastructure across the BRICS nations (Brazil, Russia, India, China, and South Africa) using an integrated Multiple Criteria Decision-Making (MCDM) approach. The primary objectives are to assess the resilience and performance of telecommunications infrastructure in these countries, identifying strengths and weaknesses through a comprehensive analytical lens. Employing a novel combination of distance-based CRITIC and modified OCRA methods within the MCDM framework, the study aims to provide a nuanced analysis of various indicators, offering a holistic view of the telecommunications landscape in these emerging economies. The research focuses on comparing and contrasting the telecommunications sectors of the BRICS nations, culminating in a ranking system where India appears as the top performer. This innovative methodological approach provides valuable insights for policymakers, contributing to strategic development and enhancement of telecommunications infrastructure in these countries. The study also outlines its limitations and recommends future research directions, including broadening the range of indicators and conducting longitudinal studies.